Does de novo hydronephrosis after pediatric robot-assisted laparoscopic ureteral re-implantation behave similarly to open re-implantation?. Issue 6 (December 2019) - Kim, Esther J.; Song, Sang Hoon; Sheth, Kunj; Baccam, Truc; Elizondo, Rodolfo; Baek, Minki; Koh, Chester J.
Summary: Background: While open ureteral re-implantation surgery is the gold standard for surgical correction of vesicoureteral reflux (VUR), robot-assisted laparoscopic ureteral re-implantation via an extravesical approach (RALUR-EV) has become a minimally invasive alternative. Previous studies have shown that transient hydronephrosis after open re-implantation can occur in up to 28% of patients. However, previous studies have also shown that de novo hydronephrosis after open re-implantation is not predictive of final differential renal function. Objective: A retrospective review was performed to characterize the natural history of postoperative hydronephrosis after RALUR-EV for primary VUR in pediatric patients. Study design: A retrospective chart review of a single-surgeon series was performed for pediatric patients who underwent RALUR-EV for primary VUR. The severity of de novo hydronephrosis was assessed using the Society for Fetal Urology (SFU) grading system via renal ultrasound at the 1-month postoperative follow-up. Renal ultrasound was performed at least every six months. Radiographic success was defined as complete resolution of VUR on the voiding cystourethrogram at the 4-month mark. Patient demographics, surgery duration, length of hospital stay, pre-operative and postoperative VUR grades, and follow-up time periods were collected. Patients with other associated urinary pathology and patients lost to follow-up were excluded from the study. Results: A total of 87 patients (121 kidney units) with primary VUR who underwent RALUR-EV met the inclusion criteria. SFU grade 1–3 hydronephrosis was noted in 30.3% (36/119) of kidney units at the 1-month mark, but 83.9% (26/31) cases with hydronephrosis completely resolved in a median time of 7.9 months (range: 3.4–21.0 months), and all four cases with unresolved hydronephrosis were downgraded to SFU grade 1 without the need for intervention. Discussion: A radiographic success rate of 96% was demonstrated in this cohort, which is comparable with that of historical open re-implantation series. A similar rate of de novo hydronephrosis was also noted in this cohort when compared with that of previous open re-implantation series, but de novo hydronephrosis after RALUR-EV had a similar or more rapid resolution rate than that previously reported after open intravesical and extravesical re-implantation series. Conclusion: De novo hydronephrosis after RALUR-EV behaves similarly to de novo hydronephrosis after open ureteral re-implantation, where de novo hydronephrosis is present in up to 30% of pediatric patients who underwent RALUR-EV. The hydronephrosis self-resolves without the need for intervention in the overwhelming majority of cases and resolves at a median time of 7.9 months after surgery. Summary Fig. Cumulative percentage of unresolved hydronephrosis with 95% confidence interval. This graph shows the cumulative percentage of unresolved hydronephrosis by months from the procedure date. HN, hydronephrosis; CI, confidence interval. Summary Fig